CdS sensitized 3D hierarchical TiO2/ZnO heterostructure for efficient solar energy conversion - Zheng, Zhaoke (2014)
For conventional dye or quantum dot sensitized solar cells, which are fabricated using mesoporous films, the inefficient electron transport due to defects such as grain boundaries and surface traps is a major drawback. To simultaneously increase the carrier transport efficiency as well as the surface area, optimal-assembling of hierarchical nanostructures is an attractive approach. Here, a three dimensional (3D) hierarchical heterostructure, consisting of CdS sensitized one dimensional (1D) ZnO nanorods deposited on two dimensional (2D) TiO2 (001) nanosheet, is prepared via a solution-process method. Such heterstructure exhibits significantly enhanced photoelectric and photocatalytic H2 evolution performance compared with CdS sensitized 1D ZnO nanorods/1D TiO2 nanorods photoanode, as a result of the more efficient light harvesting over the entire visible light spectrum and the effective electron transport through a highly connected 3D network.